Congenital malformations of the inferior vena cava and iliac - their clinical manifestations - Praderi, Raúl; Ormaechea, Carlos; Arcos Pérez, Mario; Viola, Julio; Yannicelli, Eduardo; Pollero, Héctor (Cirugía del Uruguay, 2020)
Presented at session 12th November 1962